Metabolism Characteristics of Lactic Acid Bacteria and the Expanding Applications in Food Industry - Wang, Yaqi; Wu, Jiangtao; Lv, Mengxin; Shao, Zhen; Hungwe, Meluleki; Wang, Jinju; Bai, Xiaojia; Xie, Jingli; Wang, Yanping; Geng, Weitao (Frontiers in Bioengineering and Biotechnology, 2021)
Lactic acid bacteria are a kind of microorganisms that can ferment carbohydrates to produce lactic acid, and are currently widely used in the fermented food industry. In recent years, with the excellent role of lactic acid bacteria in the food industry and probiotic functions, their microbial metabolic characteristics have also attracted more attention. Lactic acid bacteria can decompose macromolecular substances in food, including degradation of indigestible polysaccharides and transformation of undesirable flavor substances. Meanwhile, they can also produce a variety of products including short-chain fatty acids, amines, bacteriocins, vitamins and extracellular polysaccharides during metabolism. Based on the above-mentioned metabolic characteristics, lactic acid bacteria have shown a variety of expanded applications in the food industry. On the one hand, they are used to improve the flavor of fermented foods, increase the nutrition of foods, reduce harmful substances, increase shelf life, and so on. On the other hand, they can be used as probiotics to optimize the structure of the intestinal flora, relieve body inflammation, and synthesize essential nutrients. This article reviews and prospects the important metabolites in the expanded application of lactic acid bacteria from the perspective of bioengineering and biotechnology.